Replication stress links structural and numerical cancer chromosomal instability - Burrell, Rebecca A; McClelland, Sarah E; Endesfelder, David; Groth, Petra; Weller, Marie-Christine; Shaikh, Nadeem; Domingo, Enric; Kanu, Nnennaya; Dewhurst, Sally M; Gronroos, Eva; Chew, Su Kit; Rowan, Andrew J; et al. (Nature, 2013)
Cancer chromosomal instability (CIN) results in an increased rate of change of chromosome number and structure and generates intratumour heterogeneity. CIN is observed in most solid tumours and is associated with both poor prognosis and drug resistance. Understanding a mechanistic basis for CIN is therefore paramount. Here we find evidence for impaired replication fork progression and increased DNA replication stress in CIN(+) colorectal cancer (CRC) cells relative to CIN(-) CRC cells, with structural chromosome abnormalities precipitating chromosome missegregation in mitosis. We identify three new CIN-suppressor genes (PIGN (also known as MCD4), MEX3C (RKHD2) and ZNF516 (KIAA0222)) encoded on chromosome 18q that are subject to frequent copy number loss in CIN(+) CRC. Chromosome 18q loss was temporally associated with aneuploidy onset at the adenoma-carcinoma transition. CIN-suppressor gene silencing leads to DNA replication stress, structural chromosome abnormalities and chromosome missegregation. Supplementing cells with nucleosides, to alleviate replication-associated damage, reduces the frequency of chromosome segregation errors after CIN-suppressor gene silencing, and attenuates segregation errors and DNA damage in CIN(+) cells. These data implicate a central role for replication stress in the generation of structural and numerical CIN, which may inform new therapeutic approaches to limit intratumour heterogeneity.
Keywords: DNA Copy Number Variations; tumor supresorové geny; kolorektální nádory; DNA Damage; Chromosomal Instability; Cell Line, Tumor; aneuploidie; segregace chromozomů; delece genu; Colorectal Neoplasms; umlčování genů; proteiny vázající RNA; variabilita počtu kopií segmentů DNA; Chromosomes, Human, Pair 18; Gene Silencing; Nucleosides; lidé; Phosphotransferases; replikace DNA; nukleosidy; Mitosis; mitóza; lidské chromozomy, pár 18; poškození DNA; Gene Deletion; chromozomální nestabilita; RNA-Binding Proteins; fosfotransferasy; Aneuploidy; Chromosome Segregation; DNA Replication; nádorové buněčné linie; Genes, Tumor Suppressor; Humans